Variations in the hierarchical architecture of nothofagus obliqua: evidence from juvenile naturallyregenerated trees and from seedlings obtained by controlled crosses of selected individuals - Torres, Cristian Daniel; Magnin, Amaru; Gallo, Leonardo Ariel; Stecconi, Marina; Salgado, Mariana; Sosa, Claudia Maricel; Schinelli Casares, Teresa; Puntieri, Javier Guido (Scion, 2025)
Background: Many tree species with potential for wood production present high intra-specific variations in the extent of trunk differentiation (i.e. hierarchical architecture). The identification of multiple-scale traits related to hierarchical architecture could improve selection criteria for domestication. Methods: We investigated the hierarchical architecture of Nothofagus obliqua, a valuable species for timber production, but with high structural variability. Young trees in even-aged natural regeneration gaps, and seedlings derived from controlled crosses and open pollination were studied. For the second approach, trees with contrasting degree of hierarchical architecture were manually crossed. In both, juvenile plants and seedlings, we analyzed trunk growth unit traits and hierarchical architecture indices based on the relative size and branching angle of main branches. Results: In regeneration gaps, hierarchical architecture was positively related to height and diameter. Apex persistence, the number of sylleptic branches and mean internode length were indicative of larger and more hierarchical trees. Some support is provided to the idea that adult trees with a notably hierarchical architecture could produce young trees with early signs of a hierarchical architecture. In seedlings, hierarchical architecture was negatively related to basal diameter. Conclusions: Some growth unit traits that differed among progenies and were related to hierarchical architecture could be considered for the development of selection criteria for young trees.